Inferências socioculturais em fotorreportagem: estratégias pedagógicas para o 9º ano do ensino fundamental - Jesus, Flávia Renata Santos de (2021)
Teaching reading and writing in elementary school in order to make the student a critical citizen, capable of building knowledge and using it in different social communicative situations is a continuous challenge (LEFFA, 1996; SOLÉ, 1998; KLEIMAN and MORAES, 1999). That said, it is essential to look for methodologies that help students to exercise the reading activity in the face of the most varied texts, including verbal-visual ones. As the act of inferring corresponds to one of the essential aspects for the understanding of verbal and non-verbal texts (DELL’ISOLA, 1988, MARCUSCHI, 2008), this action research, according to Tripp (2005), aimed at students enrolled in the 9th year of Colégio Estadual Coelho e Campos, in the city of Capela-SE, has the general objective of developing inferences through the discourse genre of photoreport, based on social reflections , world reading and diversified activities, practical and participatory, in order to train readers capable of establishing relationships between explicit and implicit linguistic elements of a text, thus extracting reasoned and coherent meaning from it. Methodologically, the global pandemic, which affected everyone in the year 2020 and continues today, caused changes in the development of research. The work plan presented previously foresaw the application of the pedagogical proposal in the classroom, followed by the analysis and final report of the results obtained. However, with the closure of school units, it was not possible to make such planning practical. Thus, the teacher-researcher started from the development of an initial didactic sequence (according to Dolz, Noverraz and Schneuwly / 2004), to organize a Learning Support Notebook aimed, specifically, at students, in order to collaborate with didactic acquisition practices of knowledge whose purposes are related to the general objective proposed in this research work. The referred material consists on a product resulting from the Professional Master's in Language Arts and can be found in the appendix of this dissertation.